PENCIPTAAN BUKU ILUSTRASI BERBASIS POP UP TENTANG CERITA RAKYAT DANAU KASTOBA BAWEAN SEBAGAI UPAYA MEMPERKENALKAN PRODUK BUDAYA LOKAL BAGI ANAK-ANAK - Ifadhah, Hani Hani Tanzilia; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: Folklore Kastoba Lake is famous for the unique and believable as the stories that educate because were able to build and nurture local cultural values. The problem is, this story is getting increasingly rarely heard people, particularly children. Therefore, this research aims to create a book illustration-based pop up about Kastoba Lake Bawean folklore as an attempt to introduce local cultural products for children. The creation of this book using qualitative research with observation, interviewing, documentation, and existing studies are useful to define the concept of research. From the analysis results obtained the theme concept of creation that is mysterious. In that concept is a big part of the theme of the creation of this book, either from the story, the characters, the used clothing models and others. Need to be held in an attempt to attract interest read the kids against local culture folklore Kastoba Lake e.g. Bawean with different packing one of these with a book-based pop-up illustrations devoted to children and with the expectation of this pop-up book can become a media to popularize and revive Kastoba Lake folklore of Bawean to the General surrounding community as well as the Bawean especially children.Â Keywords: Mintage, book illustration, pop-ups, Bawean Kastoba Lake, Local Culture, Mysterious